Twist angle-dependent conductivities across MoS2/graphene heterojunctions - Mengzhou Liao (Nature Portfolio, 2018)
Twisting vertically stacked individual layers of two-dimensional materials can trigger exciting fundamental physics and advanced electronic device applications. Here, the authors report five times enhancement in vertical heterojunction conductivity on rotating MoS2 over graphene.